Of Planters; : an Herbarium. - Babski, Ezra; De keersmaecker, Marie; Van Rompaey, Stan (Brussels : Birthday, Felony & Fuss, 2023)
Yoon, Shun ; Wuyts, Hans ; Kim, Giseok ; Orgaer, Noëmi ; Van Beek, Orson ; Bombel, Charlotte ; Schweikle, Moreno ; Proesmans, Yen ; Kuhlmann, Hannah ; Lejeune, Delphine ; Adamski, Fritz ; Van den Meulengracht-Vrancx, Benny ; van der Meyden, Malte ; Mielech, Grazyna
Of Planters; an Herbarium, Planters, a garden show, COUR, Antwerp
boek